AN ON-LINE LIBRARY SYSTEM AN "IN-HOUSE" DEVELOPMENT - Dakshinamurti, Ganga B.; Hunter, Ken; Bozyk, Patricia; Saull, Ron (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF